2002
DOI: 10.1177/039463200201500309
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Reduces Coronary Endothelium Damage and Cardiomyocyte Necrosis but not Apoptosis after Ischemia and Reperfusion: Ex Vivo Study in Rat Hearts

Abstract: We tested the hypothesis of beneficial effects of the calcium-blocker verapamil in a model of ischemia-reperfusion, and investigated its effects against coronary microcirculation and cardiomyocyte apoptosis. Isolated working rat hearts were subjected to 15 min global ischemia and 22-180 min reperfusion in the presence or absence of verapamil (0.25 11M). We evaluated creatinephosphokinase (CK) in coronary effluent, heart weight changes, microvascular permeability (extravasation offluoresceinelabeled albumin), u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Total protection from apoptosis obtained by ZVAD-fmk in OM-treated cells could be due to the potent action of this inhibitor both on the caspases and the cysteine protease enzyme families (61). These data in addition to those concerning viability, evaluated up to 10h after removal of the drug, lead us to exclude an aspecific toxic effect of the drug (62). Other studies are necessary to increase understanding of the mechanisms leading, after in vitro treatment with OM, to caspase activation and to determine what molecular effectors, activated following lysosomal damage, are involved in the execution stage of apoptosis.…”
Section: Fl3mentioning
confidence: 91%
“…Total protection from apoptosis obtained by ZVAD-fmk in OM-treated cells could be due to the potent action of this inhibitor both on the caspases and the cysteine protease enzyme families (61). These data in addition to those concerning viability, evaluated up to 10h after removal of the drug, lead us to exclude an aspecific toxic effect of the drug (62). Other studies are necessary to increase understanding of the mechanisms leading, after in vitro treatment with OM, to caspase activation and to determine what molecular effectors, activated following lysosomal damage, are involved in the execution stage of apoptosis.…”
Section: Fl3mentioning
confidence: 91%
“…The parallel analysis of the CM morphological by light microscopy along with the trypan blue exclusion analysis showed a good correlation between cell viability and CK-MB detection. In an ex-vivo study, it has been demonstrated a clear correlation of CK release and impaired cardiomyocytes necrosis but not apoptosis after verapamil treatment of rat hearts submitted to ischemia and reperfusion procedures (Di Napoli et al 2002). Besides, it has been suggested that CK isoenzymes could be employed as the index for the infection and necrosis of the muscle in electrical injured patients due to its high specificity and sensitivity (Liu & Xie 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There are no data, on the other hand, on the long term effects of the pegylated IFN on cryoglobulinaemia. The use ofIFN in some particular clinical pictures, such as neuropathy, nephropathy and ulcers, is controversial because of its anti-angiogenic activity that can delay the healing of the ischemic lesions (11,65,68). Steroids improve the renal function and reduce proteinuria but do not affect the progression rate of the disease (11,(66)(67).…”
Section: Therapymentioning
confidence: 99%